Experimental investigation on polymer coated fibre bragg grating sensor for temperature measurement in sewer environment - Bharathi Raju; R Kumar; Samiappan Dhanalakshmi; Roman Hrbac; Lukas Demel; Narayanamoorthi R (Results in Engineering)
Environmental factors significantly influences the structural health of the massive infrastructures like Sewage plant. Under sewer environments, atmospheric factors like temperature and humidity promotes Microbial Induced Corrosion which pose serious risks to structural integrity. Robust and precise monitoring of environmental factors is indeed crucial in sewer structures to identify and mitigate conditions that accelerate Microbial Induced Corrosion (MIC), thereby ensuring the durability and structural integrity of the infrastructure. With this light of investigation, this work focuses on investigation of Fiber Optical based temperature sensor coated with polymeric material which is resilience in harsh sewer and dynamic environments. The performance of the proposed sensor is evaluated under different humid conditions in both lab and in situ environments and achieves the sensitivity of 12.9 pm/°C with the resolution and limit of detection of 0.02325 °C and 0.06979 °C respectively.